Separation investigation of endo-atmospheric multi-stage space probe. (July 2015) - Samani, M.; Ghapanvary, M. A.
Abstract: This paper deals with selection and analysis of two-stage endo-atmospheric separation of supersonic parachute of a test projectile. Flight scenario reads that after the motor burns out, it is separated from the projectile, a few moments after which the parachute is ejected out of the payload and set in the open mode. It is important to study the modes of the stages involved and set a safe distance between them. As this process involves some random variables and needs more time, a shortcut statistical method has been employed in uncertainty variables functions to carry out the analysis. It is meant to take appropriate measures in order for the separation to be collision-free and safe. To do so, relative position of the two stages are modelled and simulated. A statistical method is employed to analyse the relative distance between the two stages in critical points. The results reflect that a safe distance is maintained in the stage of parachute deployment and after supersonic parachute is employed. In addition the said analysis is also carried out via Monte Carlo method. Comparison of the results of these two methods is indicative of a small error. The statistical method is validated and sufficient knowledge on relative attitudes of the stages is obtained.